Settlement of disputes relating to the area: Role of seabed disputes chamber of international tribunal for the law of the sea - Eishan Jan, Mohammad Naqib; Hossain, Mohammad Shahadat (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The successfulresolution of maritime disputes is intertwined with the development of international legal regime concerning the oceans affairs. Transforming attention from earth based reserves wealth to the mineral resources of the seabed is a growing trend and a great concern of global community. International Seabed Authority, on behalf of all, is empowered to organize, carried out, and controlled the activities in the Area. The current article examined thelegal responsibilities, liabilities and compliance of the concerned entitiesregarding exploration and exploitation of recourse in the Area.It further explores the jurisdiction and scope of the International Seabed Authority (ISA) andSeabed dispute Chamber (SDC) of International Tribunal for Law of the Sea (ITLOS)for resolving existing potential conflictsin the Area between and among the individual, entities sponsored by the governmentin terms of interpretation and application of the relevant rules under the Sea Convention and other related agreements. Finally the aim of the research is to highlight the specific role and competency of Seabed Disputes Chamber for upholding the benefit of all mankind. Finding of the article is that the SDC made significant contribution by adopting several regulations and advisory opinion with the cooperation of other organs of the ISA. However, in order to carry out this research, author consults with the relevant international conventions and their application in resolving maritime disputes relating to the Area under international tribunals and SDC. Researcher further furnishes the information from published scholarly books and articles in the library and from onlineresources.